The Change of Some Food Elements in Soil Depending On Shadowing and Fertilization - Kravkaz Kuşçu, İnci Sevinç; Sharaf, Sayed Moqadas (Turkish Science and Technology Publishing (TURSTEP), 2021)
Soil is one of the most important factors affecting the plant development on the basis. The method mostly applied for the purpose of accelerating the plant development and ensuring the increase in products is to increase the nutrients in the soil, namely fertilization. Fertilization ensures lots of food elements in the soil to get mixed in the soil and change the soil composition. Another factor affecting the plant growth speed and productivity is shadowing. Shadow conditions change the light receiving amounts of the plant and directly affect the plant photosynthesis speed. In addition; shadowing not only affects the dissolution and in-soil mixture speed of the fertilizers applied to the soil, but it also directly affects the humidity content of the soil. In this study, it has been aimed to determine the food element changes in the soil on the lavender individuals grown under different shadow conditions and fertilized with different fertilizers. The lavender used in the study has been selected due to the fact that it adapts to dry areas, it is abstinent in terms of soil and it is an important and income-generating medical aromatic plant. As a result of the study, it has been determined that shadowing statistically affects salt, carbon, phosphor, nitrogen and potassium and fertilization statistically affects phosphor, nitrogen, potassium, carbon and salt at least at 95% confidence level.
Keywords: S; Agriculture (General); Agriculture; food substances; soil; S1-972; fertilization; shadowing; lavender; 2. Zero hunger; 15. Life on land; 6. Clean water